Kontribusi Pendidikan Agama Islam Terhadap Pembentukan Karakter Moderasi Beragama Peserta Didik - Hairunnisa; A. Zaini; Abdul Halim Rais (STAI Kuala Kapuas, 2026)
This study aims to analyze the contribution of Islamic Religious Education (PAI) in shaping the character of religious moderation in students. Religious moderation is important amidst the diversity of Indonesian society in order to create an attitude of tolerance, mutual respect, and avoid extreme attitudes. The research method used is library research by reviewing various literature, journals, books, and previous research results relevant to the topic. The results show that PAI plays a strategic role in instilling the values ​​of religious moderation through learning that emphasizes the balance between faith and tolerance, a correct understanding of religious teachings, and the cultivation of noble morals. PAI helps students have an inclusive, fair perspective and respect for differences, so they are able to interact harmoniously in social life. In conclusion, PAI contributes significantly to shaping the character of religious moderation which is the foundation for creating harmony in schools and society. It plays a role in shaping students' religious knowledge, but also becomes a strategic tool in building the character of religious moderation, which is relevant to facing the challenges of multicultural life in the global era.